Artificial Intelligence Perspective Framework of the Smart Finance and Accounting Management Model - Bani Ahmad, Ahmad Y. A.; Tiwari, Anil; Nayeem, M. A.; Biswal, Biplab Kumar; Satapathy, Debi Prasad; Kulshreshtha, Kushagra; Bordoloi, Dibyhash (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The consolidation of assets, the formation of industry alliances, and the merging of companies operating in different industries have all contributed to the introduction of cutting-edge business management systems and the formation of substantial enterprise groupings. The primary purpose of this study is to investigate, from the vantage point of AI, the steps involved in the development of an intelligent accounting management model architecture. The accounting sharing center of the platform, which provides services related to accounting sharing, is completely separate from the logistics department of any given location. The results of the experiments show that using this strategy, as opposed to the more traditional EDF, has the potential to greatly improve real-time system performance (Earliest Deadline First). Both the HVF (Highest Value First) and HVDF (Highest Value Density First) algorithms are used in every kind of workload situation. The accounting sharing center provides a variety of services to the branches of the logistics company. Some of these services include uniform and standard accounting, asset management, and currency revenue and expenditure. The pace of decrease is much more gradual when compared to both the EDF and HVF algorithms. The EDF (earliest deadline first) and HVF (highest value first) algorithms both experience a considerable slowdown in their pace of completion as the load increases. The common platform for financial management and accounting procedures does not function in a way that is closed in a single direction. One organization is in charge of each individual division.